The influence of physical exercise on College Students’ negative emotions: the mediating and regulating role of psychological resilience - Guoqing Cui; Lili Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study investigates the detrimental effects of sports culture training on negative emotions in college students, focusing on the mediating and modifying role of mental toughness. According to the "Sports Culture Training Comment Scale," "Negative Emotion Scale," "Self-efficacy Evaluation scale," and "Psychological malleability scale," the hierarchical cluster convenient and quick sampling method was used to investigate 1500 college students, and spSS20.0 and AMOS20.0 were utilized to analyze the mediating effect and the moderating effect, respectively. Positively predicting and analyzing autonomy and stamina while adversely predicting and analyzing depression, anxiety, and stress. Independence and Physical Despair Predict and analyze anxiety, depression, and stress. Regarding the association between physical activity and negative emotions, the mediating effects of independence and psychological resilience contributed 26.78 percent and 31.33 percent, respectively, to the total benefits. Mental exercise's independence and adaptability are crucial in physical activity and unpleasant emotions. Training in sports culture increased college students' self-efficacy and mental toughness and effectively prevented and reduced negative feelings.